First analysis of life history and season of death of a South American gomphothere. (2nd July 2017) - El Adli, Joseph J.; Fisher, Daniel C.; Cherney, Michael D.; Labarca, Rafael; Lacombat, Frédéric
Abstract: Excavations associated with wastewater treatment facilities in the Santiago Basin of Chile uncovered remains of an adult male Stegomastodon platensis in Pleistocene fluvial sediments. The specimen included a skull with both tusks still in their alveoli. A small sample block of dentin and cementum was excised from the right tusk for analysis of compositional and structural variation recorded in the sequence of dentin layers. The sample was analyzed using serial isotope assays, microCT, and measurement of dentin increments in thin sections. These procedures allowed us to recover life history information relating to the final four years of life. Analyses show seasonal variation in composition, density, and growth rate, permitting identification of years. MicroCT features appear to recur semiannually, which has not been observed previously in proboscidean tusks; these features are interpreted to correspond to the winter-spring boundary and some other aspect of environment or behavior recurring within each year. Average annual apposition of dentin within the tusk is 10.4 mm for complete years studied, suggesting that this individual was healthy leading up to the final year of life. Recurrent periods of low rate of apposition measured in weekly dentin increments that formed during the summer are interpreted as representing periods of musth. Using the location of microCT features, annual appositional thickness, and the pattern of weekly growth within the final year of life, we interpret the season of death for this individual as being within the early autumn.